CRIMINAL LAW ENFORCEMENT AGAINST PERPETRATORS OF ILLEGAL MINING IN SUKODADI VILLAGE, KABUH, JOMBANG - Yudha; Subekti; Soekorini, Noenik (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
This research aims to analyze the criminal liability and law enforcement process against perpetrators who carry out unlicensed mining activities in Sukodadi village, Kabuh, Jombang. This research is included in sociological and legal research. The results indicated that the perpetrators fulfilled the elements of liability. In this case, the mistake considers intentionality and negligence, which means that the perpetrators are considered to have intentionality committed the act. Thus the perpetrators, in taking responsibility for their actions, can be subject to Article 160 paragraph 2 of the Law of the Republic Indonesia No. 4/2009 concerning Mineral and Coal Mining Jo Article 55 Paragraph 1 to (1) of the Criminal Code with a maximum imprisonment of 5 (five) years and a maximum fine of IDR. 10,000,000,000,- (ten billion rupiah). The law enforcement process against the perpetrators conducted by the East Java Police Special Criminal Investigation Unit, namely conducting, summoning, confiscation, and searches in this case, is very supportive and mutually reinforcing between witness testimony, expert testimony, clues, and the existence of evidence seized with the confession of the suspect.